How sustainable are cultural organizations? A global benchmark - Martin Müller; Julie Grieshaber (Sustainability: Science, Practice, & Policy)
Museums, theaters, and other cultural organizations can be important actors in the sustainability transition, enjoying high visibility and public trust. Yet, we know little about their performance with respect to key sustainability indicators. This study develops a sector-specific sustainability benchmark and applies it in a survey of 206 leading cultural institutions worldwide and 21 semi-structured interviews. The results show that, for the majority of organizations, sustainability did not appear as a management issue until approximately five years ago. Moreover, sustainability commitments do not translate consistently into action. More than half of the organizations obtain poor sustainability scores of below 30 (out of 100) on both the environmental and the social dimension. The presence of a green team and government regulation are associated with higher sustainability scores. Our findings suggest the need for a concerted approach to sustainability in the cultural sector, including a common standard, regular monitoring (for example using this benchmark), and incentivized funding.